Dental Professional’s Knowledge, Preventive Awareness and Attitude Towards COVID-19 in Saudi Arabia: A Cross-Sectional Survey - Alwazzan RA; Baseer MA; ALMugeiren OM; Ingle NA (Dove Medical Press, 2021)
Rayyan Abdallah Alwazzan, Mohammad A Baseer, Osamah Mohammed ALMugeiren, Navin Anand Ingle Department of Preventive Dentistry, College of Dentistry, Riyadh Elm University, Riyadh, Saudi ArabiaCorrespondence: Mohammad A BaseerDepartment of Preventive Dentistry, College of Dentistry, Riyadh Elm University, Namuthajiya Campus, PO Box No. 84891, Riyadh, 11681, Saudi ArabiaEmail ma_baseer@riyadh.edu.saBackground: Given the COVID-19 pandemic, it is necessary to assess the dentist’s knowledge, preventive awareness, and attitude towards COVID-19 in Saudi Arabia. This study aimed to assess dental professionals’ knowledge, preventive awareness, and attitude towards dental care during the COVID-19 pandemic in Saudi Arabia.Study Subjects and Methods: The study participants consisted of dental professionals working in government, private and academic sectors in Saudi Arabia. An online questionnaire (Whatsapp and Twitter) was sent to dental professionals in July 2020. The questionnaire consisted of questions on dental professional’s demographic variables, their knowledge of the incubation period, the symptoms, mode of transmission, preventive awareness of COVID-19, and their attitude toward treating patients with COVID-19. Mann–Whitney U and Kruskal–Wallis tests were applied to compare mean ranks and a p< 0.05 is considered statistically significant.Results: This study included a total of 356 dental professionals (dentists and dental students) aged 22– 60 years (mean±SD, 32.14± 7.48 years). Majority of the participants were graduates/general practitioners (GP) 145 (40.7%), followed by post graduate (PG) student 108 (30.3%), undergraduate students 23 (6.5%) and specialist 80 (22.5%). Dental professionals showed a high level (> 90% correct responses) of knowledge of COVID-19 except for the infection among comorbid patients 283 (79.5%) and incubation period of COVID-19, 164 (46.1%). An overall high knowledge of COVID-19 (87.26%), preventive awareness (88.64%) and a positive attitude (65.26%) towards dental care were observed among the study participants. The mean knowledge ranks differed significantly in different genders (p=0.029) and marital status (p=0.023), whereas preventive awareness differed significantly across various qualifications (p=0.004). The mean attitude rank was significantly higher among Saudi (182.29) compared to non-Saudi (141.36) study participants (p=0.025).Conclusion: The dental professionals participated in this study demonstrated adequate knowledge of symptoms, preventive awareness, and a positive attitude towards dental care of the COVID-19 infected patients.Keywords: attitude, awareness, COVID-19, dental professional, knowledge